Changes in natural haemolytic complement activity induced by stress in gilthead seabream (Sparus aurata L.). Issue 78 (July 2018) - Guardiola, Francisco A.; Saraiva-Fraga, Miguel; Cuesta, Alberto; Esteban, M. Angeles
Abstract: In aquaculture, animals can be continually exposed to environmental stress factors that put their health and even survival at risk. Two experiments were performed to evaluate the impact of different stress conditions (acute crowding and anaesthetic) on the natural haemolytic complement activity in serum and skin mucus of gilthead seabream ( Sparus aurata L.). In the first experiment, fish were subjected to 10 kg m −3 (low density, control group) and 50 kg m −3 (high density, crowding group) during 2, 24 and 48 h. In the second experiment, fish were unexposed (control) or exposed to 40 ppm of MS-222 or 5 ppm or 10 ppm of clove oil for 1 h. In fish maintained in acute crowding conditions only an increase of the haemolytic complement activity was observed in the skin mucus after 24 h of exposure. However, a similar statistically significant increase was observed in serum and skin mucus of fish exposed for 1 h to the lowest concentration of clove oil (5 ppm) tested. The results point to a new and alternative way to assess stress in farmed fish by using skin mucus instead of blood serum and confirm that the measurement of natural haemolytic complement activity serves as an indicator of stress in fish. Graphical abstract: Image 1 Highlights: A better understanding of the relation between the fish complement system and stress was achieved. Complement activity responds differently in serum and skin mucus under acute crowding situations. Exposure to clove oil (5 ppm) for 1 h stimulates haemolytic complement activity in serum and skin mucus. Skin mucus haemolytic complement activity is a potential low-invasive indicator of stress in fish.